Open Promotion of the Regional Secretary of Sambas Regency: Perspectives on Siyasah Jurisprudence and Legislation in Indonesia: Open Promotion Sekda Kabupaten Sambas: Perspektif Fikih Siyasah dan Perundang-Undangan di Indonesia - Lubis, Ali Akhbar Abaib Mas Rabbani (Institut Agama Islam Negeri (IAIN) Pontianak, 2020)
This paper discusses the implementation of the open promotion of the Regional Secretary (Sekda) of Sambas Regency in 2017, the reign of Atbah Rohim Suhaili in the 2016-2021 period. This got a response from Governor of West Borneo regarding the actions of the Bupati who did not comply with procedures or did not first consult with the Governor. Even though, the open promotion was successfully implemented on a national scale. However, the implementation of the open promotion was not confirmed by the evidence of results or the value of open and competitive selection by the official website of the Sambas Regency Government (sambas.go.id). This research is included in a qualitative cluster with a statute approach which involves the siyasah dusturiyah in the fiqh siyasah study cluster and is complemented by the fieldwork approach. The result is that the stages of the open promotion of JPT Pratama Regional Secretary of Sambas Regency have been carried out in accordance with the Act of 2014 Law, the stages in the description of the implementation of Sambas Regional Secretary’s open promotion in general, if it is connected with Islamic principles there is certainly no prohibition. The appointment process in the leadership of Khulafa al-Rasyidin also had different ways of implementation and stages, so that there were no standard stages of implementation regulated in Islam. In addition, ASN Act 2014 and the implementation of the open promotion of the Regional Secretary of Sambas Regency are viewed more carefully and deeply. There are several findings that need to be explained here. Moreover, ASN Act of 2014 and the implementation of the open promotion of the Regional Secretary of Sambas Regency are not infallible without weakness (fallible). The findings obtained are confusion and inconsistency in the ASN Act of 2014.